Desinfecção solar de água para comunidades de baixa renda - Felix, Lorna Falcão (2010)
The use of solar energy for water disinfection, and is accessible to disadvantaged communities because of its low cost, has the advantage of using disposable materials such as bottles of polyethylene terephthalate (PET). We present a study that used two methods of disinfection: the methodology proposed by the project Solar Water Disinfection (SODIS), which consisted of water disinfection by solar radiation and temperature and the methodology which the temperature of the water for disinfection. In both, we seek to eliminate microorganisms that cause serious diseases such as dysentery, typhoid, cholera, etc. Water samples were collected in the community of Bass, where the population has low income and the incidence of waterborne diseases is high. The experiments were divided into two stages. In step 1 we studied the feasibility of disinfection and in step 2 the feasibility of the pilot plant to obtain adequate levels of disinfection temperatures desired. The results showed the efficiency of the disinfection process, reaching an average of 80 to 100% death of microorganisms, but regrowth was observed in some samples. Finally on the good results of stage 1, is designed and built and tested in an experimental pilot plant, which has shown to be feasible to promote water disinfection through the use of solar energy. The water after treatment is in accordance with the limits established by Brazilian legislation for clean water, maintaining a positive performance for the disinfection and acceptable levels of bacterial regrowth